The Paleolithic open-air site of Tolbor-17 (Mongolia): A preliminary faunal report (Studia Archaeologica, 2025)
The open-air site of Tolbor-17 (T17), located in northern Mongolia, contains one of few faunal assemblages in the region from early Marine Isotope Stage 3 (MIS 3, ~57-29 ka cal BP). During this period, humans migrated into northern Asia as part of the Initial and Early Upper Paleolithic (IUP and EUP). Much is still unknown about these populations, including the adaptive strategies that facilitated their success at the geographic margins of hominin dispersal. This paper presents the preliminary analysis of the T17 faunal assemblage, a valuable source of data on early human subsistence and paleoecology. Although small (n = 836) and fragmentary, the assemblage illuminates several aspects of early human behavior, namely the butchery of large and extra-large ungulates as well as the use of osseous tools and personal ornaments. In addition to ungulates, humans also exploited marmot, ostrich (eggshell) and at least one large carnivore, attesting to the wide range of human-animal interactions at the site. In addition to humans, carnivores also modified the assemblage, likely as scavengers of human butchery waste. These results provide a basis for future analyses at the site, focusing on the agents of accumulation, taphonomic processes, and implications for early human adaptations in Central Asia.